Metagenomic Sequence of Prokaryotic Microbiota from an Intermediate-Salinity Pond of a Saltern in Isla Cristina, Spain - Fernández, Ana B. (American Society for Microbiology, 2014)
Marine salterns are artificial multipond systems designed for the commercial production of salt by evaporation of seawater. We report here the metagenomic sequence of the prokaryotic microbiota of a pond with intermediate salinity (21% total salts) of a saltern located in Isla Cristina, Huelva, southwest Spain.